LC-MS/MS-Based Concurrent Quantification of Cannabidiol and Melatonin in Mouse Plasma to Elucidate Complex PK Interactions - Mengran Wang; Wenpeng Zhang; Xia Wu; Lingchao Wang; Cong Li; Chunyan Liu; Xiaomei Zhuang (Pharmaceutics)
Objective: This study aimed to develop a quantitative analytical method for the simultaneous determination of cannabidiol (CBD) and melatonin (MT) in mouse plasma using the protein precipitation method coupled with LC-MS/MS. Additionally, this study sought to investigate the impact of CBD on the pharmacokinetics of MT in mice using this method. Methods: Mouse plasma samples were precipitated with acetonitrile and analyzed using a Kromasil 100-5-C8 (2.1 × 50 mm) column. Following a single administration, thirty male ICR mice were randomly assigned to five groups: MT 2 mg/kg intravenously (i.v.), MT 10 mg/kg orally (p.o.), MT + CBD (10 + 10) mg/kg p.o., MT + CBD (10 + 40) mg/kg p.o., and MT 10 mg/kg p.o. followed by CBD 2 mg/kg i.v. Pharmacokinetic parameters were calculated using a non-compartmental model and analyzed to investigate the interactions of CBD with MT. Results: The calibration curves for CBD and MT were linear over the range of 2 to 1000 ng/mL. Co-administration of a high dose of CBD (40 mg/kg) orally reduced the Cmax of MT (10 mg/kg) to 57% of the control, while the area under the curve from 0.5 to 8 h (AUC(0.5–8h)) was 2.85-fold that of the MT-only group. When CBD (2 mg/kg) was administered intravenously alongside MT orally, the AUC(0.5–8h) was 1.54 times that of MT given orally alone. The AUC of CBD was positively correlated with the AUC of the distribution and elimination phases of MT, while the Cmax of CBD negatively correlated with the Cmax of MT. Conclusions: The developed LC-MS/MS method is robust and suitable for pharmacokinetic studies involving CBD and MT. The in vivo effects of CBD on MT pharmacokinetics are complex. High oral doses of CBD inhibit both the intestinal absorption and metabolic clearance of MT, resulting in a more smooth PK profile.